Implementasi Model Student Team Achievement Division (STAD) Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa - Jaenal Aripin; Sulistyono Sulistyono; Uus Toharudin (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
The background of this research is that learning tends to a cursory understanding, not touching the problems that exist in the environment. This situation occurs when the learning is considered.learning process is only centered on the teacher, students in passive conditions, not actively engaged only to hear And writing what the teacher explained. This causes the students are not eager in learning. The purpose of this research is to know the implementation of learning model Student Team Achievement Divison (STAD) to creativity and student learning outcomes, materials classification of woody plants, improving student creativity, Student learning, and student responses at MTs Maarif Cipakem Maleber District. The research method used is experiment, that is one experiment group using Student Team Achievement Divison (STAD) and one control group using lecture method. Implementation of the model (STAD) results of a group of students, teacher presentations, group assignments, tests, comparisons, and rewards. The results obtained from the Students for the average number of post-test experimental class 73.66 is greater than the average post-test class control 19,81, the average number of increase in value (N gain) experimental class 4.94 more Large from the average number of increments (N gain) control class 1.42. That is, there is a difference of students' learning outcomes with the control class. The experimental class students had a higher gain (N gain) than the control class students. While the average creativity of the experimental class students was 72, 81 was greater than the average creativity of the control class students 58,84. Significant between student learning outcomes in experimental class and control classKeywords: Learning Model STAD; Creativity; Learning Outcomes